PENULISAN FEATURES DI MEDIA DARING RADAR MADURA - Muzammil, Ach; syamsudin, syamsudin; khoirudin, Khoirudin (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2021)
Online media comes with a variety of conveniences offered to its readers. The feature still includes a soft news style so it's light and easy to understand. So that the writing is flexible but not too straightforward, not too stiff. In the delivery of features will create a sense of value. Important events tend to be conveyed carefully, straightforwardly and directly to the point, so that people who receive the news are immediately able to catch what is happening, while less important events may be presented in a riddle, often accompanied by jokes. This research refers to the high reading interest of the Madurese community in the era of the Covid-19 pandemic which encouraged people to carry out activities at home, one of which was to obtain information. The scientific reason why the author chooses Feature to be discussed is because according to an analysis by one of Radarmadura.id's own journalists, Feature news has quite a high audience because of the elements of the style of the news which are relaxed and easily understood by all levels of society. What's more, raising local Madurese human interests will attract readers from those who are interested in the figures in the published features.